ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS DAN KEAKTIFAN SISWA SMA DENGAN PENDEKATAN PROBLEM POSING - Arista Merdian; Veny Triyana Andika Sari; Asep Ikin Sugandi (LP2M Universitas Sarjanawiyata Tamansiswa, 2018)
The background of this research problem, starting from the still low ability of mathematical communication and the activity of high school students. The purpose of this research is to describe the improvement of mathematical communication ability and activity of class X students of SMA Muhamadiyah 1 Cimahi. Design Research conducted a classroom study using John Elliot's model. The research flow has two cycles, each cycle consisting of planning, execution, observation and reflection. The result of this research is that there is improvement of mathematical communication ability and activeness by applying problem posing approach on learning mathematics about SPLTV in SMA Muhammadiyah 1 Cimahi class X, for the improvement of mathematical communication ability viewed based on percentage of students whose value is below KKM, equal to KKM, and above the KKM sequentially respectively by 9.68%, 54.84%, and 96.77%. To increase student activeness can be seen based on percentage of students who have active active value and very active in cycle I and cycle II, respectively equal to 35,48% and 93,54%.